Safety and effectiveness of collagenase clostridium histolyticum in the treatment of Peyronie's disease using a new modified shortened protocol. (14th July 2017) - Abdel Raheem, Amr; Capece, Marco; Kalejaiye, Odunayo; Abdel‐Raheem, Tarek; Falcone, Marco; Johnson, Mark; Ralph, Oliver G.; Garaffa, Giulio; Christopher, Andrew N.; Ralph, David J.
Abstract : Objectives: To evaluate the efficacy and safety of collagenase clostridium histolyticum (CCH; Xiapex ®, Xiaflex ® ) in the treatment of Peyronie's disease (PD) using a new modified treatment protocol that aims at reducing the number of injections needed and reducing patient visits, thus reducing the duration and cost of treatment. Patients and Methods: A prospective study of 53 patients with PD who had treatment with CCH at a single centre using a new modified protocol. The angle of curvature assessment after an intracavernosal injection of prostaglandin E1, the International Index of Erectile Function (IIEF) and Peyronie's Disease Questionnaire (PDQ) were completed at baseline and at week 12 (4 weeks after the last injection). The Global Assessment of Peyronie's disease (GAPD) questionnaire was completed at week 12. Under a penile block of 10 mL plain lignocaine 1%, a total of three intralesional injections of CCH (0.9 mg) were given at 4‐weekly intervals using a new modified injection technique. In between injections patients used a combination of home modelling, stretching and a vacuum device on a daily basis to mechanically stretch the plaque. Investigator modelling was not performed. Results: The mean (range) penile curvature at baseline was 54 (30–90)°. Of the 53 patients in the study, 51 patients (96.2%) had an improvement in the angel of curvature by a mean (range) of 17.36 (0–40)° or 31.4 (0–57)% from baseline after three CCH injections. The final mean (range) curvature was 36.9 (12–75)° ( P < 0.001). There was an improvement in each of the IIEF questionnaire domains, all three PDQ domains and the GAPD. CCH was well tolerated by all patients with only mild and transient local adverse events. Conclusion: The new shortened protocol using CCH treatment is safe, effective, and cost efficient. The results of using only three CCH injections according to this modified protocol are comparable to those of the clinical trials that used eight CCH injections.